ANALISIS LINGKUNGAN SEKOLAH TERHADAP KREATIVITAS SISWA - Yulia Mariam Sapariani; Yennie Indriati Widyaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The school environment plays a strategic role in supporting the learning process and fostering students’ creativity, particularly at the elementary education level. In response to the demands of 21st-century education, creativity has become a key competency that must be developed through a supportive learning environment, encompassing both physical and non-physical aspects. However, empirical evidence indicates that many schools have not yet optimally utilized the school environment as a learning resource. This study aims to examine the role of the school environment in enhancing students’ creativity at SDN Regol 7 Kiansantang. A qualitative approach with a descriptive case study design was employed. Data were collected through observations, interviews, and documentation, and data credibility was ensured through triangulation techniques. The findings reveal that a well-maintained and effectively utilized school environment contributes to increased student engagement, learning motivation, and creativity. The integration of indoor and outdoor learning spaces, including classrooms, libraries, greenhouses, and schoolyards, provides authentic and meaningful learning experiences. Nevertheless, the implementation of environment-based learning requires careful instructional planning and effective classroom management to maintain focused and structured learning activities. Overall, the study concludes that a conducive school environment has a positive impact on the development of students’ creativity.